IMPROVING POETRY WRITING COMPETENCE THROUGH PROJECT-BASED LEARNING: A CLASSROOM ACTION RESEARCH AT SMK NEGERI INANWATAN, SOUTH SORONG - Marselino Laiyan; Justien R. Wuisang; Jourike Runtuwarouw (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2025)
This study investigates the effectiveness of Project-Based Learning (PjBL) combined with a digital detox strategy and print-based cognitive scaffolding in improving the poetry writing competence of vocational high school students. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart spiral model, the study was conducted across two cycles with 15 Class X students of the Computer and Network Engineering (TKJ) program at SMK Negeri Inanwatan, South Sorong, Southwest Papua, Indonesia. Poetry writing competence was assessed across five indicators: diction, figurative language, rhyme and rhythm, theme, and moral message. Results demonstrated a consistent and significant improvement across all phases: the class mean rose from 68.49 (pre-cycle) to 73.05 (Cycle I) and reached 81.66 (Cycle II), while classical mastery improved from 20% to 40% and ultimately to 80%, surpassing the 75% success criterion. The digital detox strategy proved instrumental in eliminating copy-paste behavior and promoting authentic, observation-based literary expression. Three print-based scaffolding tools introduced in Cycle II (a Word Wall, a Figurative Language Pocket Book (Buku Saku Kiasan), and a curated poetry anthology) functioned as effective cognitive scaffolds that bridged students' technical-denotative language habits and the aesthetic-connotative demands of poetry. These findings demonstrate that literary creativity among technically-oriented vocational students is not inherently limited but is highly responsive to contextually adapted, structure-rich pedagogical interventions. The study contributes a replicable, resource-light instructional model for Indonesian language arts teachers in vocational education contexts.